Education Management in the Independent Curriculum in Elementary Schools - Jenny Fransiska; Dumiyati Dumiyati; Popon Mariam; Nurul Hikmah; Muhammad Haris (al-fikrah: Jurnal Manajemen Pendidikan, 2023)
Education is the most important pillar in a nation, where the goals contained in education are to be able to educate the nation's life and also be able to nurture all the achievements and potential that exists within each student, so that later they can become good and superior individuals to be able to compete, both in the national and international arena. Every existing educational institution must have a learning curriculum, because the curriculum is a design and arrangement that guides the continuity of education. The purpose of the study was to analyze how the independent curriculum forms in education management in an elementary school. This research uses a qualitative approach method with a descriptive form, which emphasizes more on explanatory and explanatory studies. Data collection techniques are carried out by means of interviews, and observation, the data is obtained by describing the opinions of the samples from the results of interviews conducted directly. The results showed that the independent curriculum in an educational management in elementary schools can run very well, safely and there are not many obstacles faced. Because the application of the independent curriculum in elementary schools makes students quite challenged and welcomes it well. Because the curriculum is something very new for students, many are enthusiastic about it. The weaknesses contained in the research are that the researchers did not visit many elementary schools, because they only focused on one place and on one of the students. for that further researchers are expected to have many other samples.